2002
DOI: 10.1034/j.1399-6576.2002.460817.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the analgesic effect of tramadol, tramadol plus magnesium, and tramadol plus ketamine for postoperative pain management after major abdominal surgery

Abstract: Adding magnesium or ketamine to tramadol improved analgesia and patient comfort and decreased the amount of tramadol required for postoperative pain management after major abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Accordingly, intrathecally administered NMDA receptor antagonists produce antinociception on thermal, chemical and neuropathic pain tests [55] . In line with this evidence, ketamine, a nonselective NMDA receptor antagonist, improved tramadol analgesia and patient comfort and decreased the amount of tramadol required for pain management in abdominal surgery [5] . As previously mentioned, gabapentin is able to affect glutamatergic neurotransmission by reducing glutamate release and Ca 2+ infl ux by different mechanisms which includes the closing of voltage-dependent Ca 2+ channels.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Accordingly, intrathecally administered NMDA receptor antagonists produce antinociception on thermal, chemical and neuropathic pain tests [55] . In line with this evidence, ketamine, a nonselective NMDA receptor antagonist, improved tramadol analgesia and patient comfort and decreased the amount of tramadol required for pain management in abdominal surgery [5] . As previously mentioned, gabapentin is able to affect glutamatergic neurotransmission by reducing glutamate release and Ca 2+ infl ux by different mechanisms which includes the closing of voltage-dependent Ca 2+ channels.…”
mentioning
confidence: 75%
“…Tramadol is effective in reducing moderate to severe postoperative pain with an overall effi cacy similar to that of morphine or alfentanil. Previous clinical studies have shown that adding magnesium, ketamine [5] [6] or acetylsalicylate [7] to tramadol improved analgesia and patient comfort and decreased the amount of tramadol required for pain management. Studies in animals supporting these interactions are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs, opioid agonist-antagonists and mixed analgesics like tramadol, with and without magnesium, have also been used successfully. [5][6][7] Use of the anesthetic agent ketamine has also been reported during PCA. Ketamine has been used in conjunction with a variety of different analgesic agents intravenously, epidurally, and during wound infiltration via a patient-controlled delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium sulfate has also been previously investigated as a possible adjuvant for postoperative analgesia [13][14][15][16][17][18][19][20][21][22][23] . However; relatively few studies have been conducted on the effects of postoperative intravenous magnesium administration (as an infusion) over a 24-hour period 17,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…However; relatively few studies have been conducted on the effects of postoperative intravenous magnesium administration (as an infusion) over a 24-hour period 17,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%